Introduction to the special issue: Fatness and temporality. Issue 2 (4th May 2018) - Tidgwell, Tracy; Friedman, May; Rinaldi, Jen; Kotow, Crystal; Lind, Emily R.M.
ABSTRACT: As scholars, artists, and activists continue to contend with the question of who has a future, we are drawn to the relationship between fat and the social construction of time. In this introduction to the special issue of Fat Studies: An Interdisciplinary Journal of Body Weight and Society, we explore what fat reveals about time and what fat studies offers to current conceptions of temporality. We consider how fat existence and fat interventions cultivate temporal economies other than linear, capitalist, colonial ones, and reflect on how fat studies scholarship is amplified and reconfigured by intersecting ways of knowing about time through the lived experience of fatness.